ESG as a Competitive Intelligence Source in the Shipping Industry - Kanellopoulos, Anastasios Nikolaos (HAPSc Policy Briefs Series, 2024)
The present paper explores the emerging role of Environmental, Social, and Governance (ESG) factors as a potent source of Competitive Intelligence (CI) within the Shipping industry. With increasing global focus on sustainability and responsible corporate practices, stakeholders in Shipping are recognizing the significance of integrating ESG considerations into their strategic decision-making processes. This paper investigates how ESG data can serve as a valuable tool for gaining competitive advantage, enhancing risk management, and fostering long-term sustainability within the Shipping industry. Through a comprehensive review of literature, case studies, and industry reports, this paper offers insights into the evolving landscape of ESG implications for CI in Shipping.